The Effect of Academic Service Quality on Student Satisfaction Level Stikes Panrita Husada Bulukumba - Tenri Aben; Muriyati; Edison Siringoringo (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Higher education is a form of service provider that involves providers and service users. The quality of a tertiary institution is largely determined by the quality of services provided, such as high achievement motivation, lecturer competence, roles, assignments, and facilities and infrastructure. Good infrastructure is expected to create institutions that are clean, beautiful, and comfortable, so they need to be managed properly. The method used was a descriptive research design with a